The Development of Bahasa Indonesia Thematic Teaching Materials Integrated with Islamic Values Based on Flipbook Maker at Madrasah Ibtidaiyah Nurus Syakur Ledokombo Jember - Fandrik Haris Setia Putra (EDUCARE: Journal of Primary Education, 2022)
Developing teaching materials that are integrated with Islamic values is a necessity. Therefore, one of the tasks of educators is to instill values. The integration of Islamic values can be applied to various learning, including Bahasa Indonesia learning that can be packaged in the form of Flipbook Maker-based digital teaching materials. This study aims: (1) to describe the validity and attractiveness of Bahasa Indonesia teaching materials integrated into Islamic values-based Flipbook Maker, (2) to determine the effectiveness of Indonesian teaching materials integrated into Islamic values-based Flipbook Maker. The method used is research and development of the Borg and Gall model with the following steps: (1) problem identification, (2) Information Collection, (3) Product Design, (4) design validation, (5) design improvement, (6) product testing, (7) product Revision (8) usage testing (9) Product Improvement (10) dissemination and implementation. The results of the expert validation test showed an average level of validity of 91.3%, with details of material validation of 90%, language validation of 96%, and design validation of 88%. Thus teaching materials are an excellent criterion. At the same time, the response of interest in teaching materials from educators is 88.6%, and 93.3% of learners with excellent standards. Posttest results showed that the average learning outcome of Group A was 76.18 while Group B was 64.71. The difference in learning outcomes between Group A and Group B was 11.47. At the same time, the analysis showed the value of GIS. (2-tailed) is 0.000 < 0.05 and t count > t table (5.607 > 2.120). Thus Bahasa Indonesia teaching materials integrated Islamic values based Flipbook Maker effective to use. Mengembangkan bahan ajar yang terintegrasi dengan nilai-nilai keislaman merupakan sebuah keniscayaan. Sebab, salah satu tugas pendidik adalah menanamkan nilai-nilai. Integrasi nilai-nilai keislaman dapat diterapkan ke dalam berbagai pembelajaran, termasuk pembelajaran Bahasa Indonesia yang dapat dikemas dalam bentuk bahan ajar digital berbasis Flipbook Maker. Penelitian ini bertujuan: (1) mendeskripsikan validitas dan kemenarikan bahan ajar Bahasa Indonesia terintegrasi nilai-nilai keislaman berbasis Flipbook Maker, (2) mengetahui efektifitas bahan ajar Bahasa Indonesia terintegrasi nilai-nilai keislaman berbasis Flipbook Maker. Metode yang digunakan adalah penelitian dan pengembangan model Borg and Gall dengan langkah-langkah sebagai berikut: (1) identifikasi masalah, (2) pengumpulan informasi, (3) desain produk, (4) validasi desain, (5) perbaikan desain, (6) uji coba produk, (7) revisi produk (8) Uji coba pemakaian (9) penyempurnaan produk (10) deseminasi dan implementasi. Hasil uji validasi ahli menunjukkan tingkat rata-rata validitas 91,3% dengan rincian validasi materi 90%, validasi bahasa 96%, dan validasi desain 88%. Dengan demikian bahan ajar berada pada kriteria sangat baik. Sementara respons kemenarikan bahan ajar dari pendidik 88,6% dan peserta didik 93,3% dengan kriteria sangat baik. Hasil posttest menunjukkan rata-rata hasil belajar kelompok A sebesar 76,18 sedangkan kelompok B sebesar 64,71. Selisih perbedaan hasil belajar antara Kelompok A dan Kelompok B adalah 11,47. Sedangkan hasil analisis menunjukkan bahwa nilai sig.(2-tailed) adalah 0,000 < 0,05 dan t hitung > t tabel (5,607 > 2,120). Dengan demikian bahan ajar Bahasa Indonesia terintegrasi nilai-nilai keislaman berbasis Flipbook Maker efektif untuk digunakan.